Prevalence of Batrachochytrium dendrobatidis in Xenopus collected in Africa (1871-2000) and in California (2001-2010). - Vance T Vredenburg (Public Library of Science (PLoS), 2013)
International trade of the invasive South African clawed frog (Xenopus laevis), a subclinical carrier of the fungal pathogen Batrachochytrium dendrobatis (Bd) has been proposed as a major means of introduction of Bd into naïve, susceptible amphibian populations. The historical presence of Bd in the indigenous African population of Xenopus is well documented. However, there are no reports documenting the presence of Bd in wild Xenopus populations in the US, particularly in California where introduced populations are well-established after intentional or accidental release. In this report, a survey was conducted on 178 archived specimens of 6 species of Xenopus collected in Africa from 1871-2000 and on 23 archived specimens (all wild-caught Xenopus laevis) collected in California, USA between 2001 and 2010. The overall prevalence rate of Bd in the tested Xenopus was 2.8%. The earliest positive specimen was X. borealis collected in Kenya in 1934. The overall prevalence of Bd in the X. laevis collected in California was 13% with 2 positive specimens from 2001 and one positive specimen from 2003. The positive Xenopus (3/23) collected in California were collected in 2001 (2/3) and 2003 (1/3). These data document the presence of Bd-infected wild Xenopus laevis in California. The findings reported here support the prevailing hypothesis that Bd was present as a stable, endemic infection in Xenopus populations in Africa prior to their worldwide distribution likely via international live-amphibian trade.